Applied Sunnah During Hot Weather And Rainy Season: The Philosophy Of Faith And Mitigation Measures - Azwira Abdul Aziz; Abdul Rasydan Mohamad Rusli (Universiti Sains Islam Malaysia, 2025)
Journal Of Hadith Studies,Volume 9 Issue 2 Page (108-120)